Gripping ease in southern green stink bugs Nezara viridula L. (Heteroptera: Pentatomidae): Coping with geometry, orientation and surface wettability of substrate. Issue 1 (16th January 2019) - Voigt, Dagmar; Perez Goodwyn, Pablo; Sudo, Masaaki; Fujisaki, Kenji; Varenberg, Michael
Abstract: The southern green stink bug Nezara viridula L. (Heteroptera, Pentatomidae) is highly polyphagous, preferring apically situated seeds and fruits on more than 150 plant species belonging to over 30 plant families all over the world. This forces them to move over highly variable terrains, including plant stems, leaves, pods and buds, which requires efficient attachment. Stink bugs have long slender legs and feet (tarsi) equipped with paired curved claws, paired soft adhesive pads (pulvilli), and flattened lanceolate hairs (setae), which arise ventrally on the first and second foot segments (tarsomeres). To characterize their attachment abilities on well‐defined test substrates, here we comparatively measured and analyzed the traction forces of bugs walking horizontally and vertically on hydrophilic (water attractive) and hydrophobic (water repellent) glass plates and rods. The latter correspond to the geometry of preferred feeding sites of stink bugs in the field. The results show a clear contribution of tarsal flattened lanceolate hairs to the stink bug's attachment. Higher traction forces are generated on a glass rod than on a glass plate, corresponding to up to individual maximum of 43 times the stink bug's body weight. Substrate hydrophobicity promotes the attachment, while the measured forces are up to eight times lower when tarsal hairs are disabled. The combination of smooth and hairy tarsal pads results in a remarkable attachment ability, which enables N. viridula to climb unstable apical plant parts, and supports their invasive behavior and global dispersion. Abstract : Southern green stink bugs generated higher traction forces on a glass rod than on a glass plate, corresponding to up to individual maximum of 43 times the stink bug's body weight. Substrate hydrophobicity promotes the attachment, while the measured forces are up to eight times lower when tarsal hairs are disabled. The combination of smooth and hairy tarsal pads results in a remarkable attachment ability, which enables Nezara viridula to climb unstable apical plant parts, and supports their invasive behavior and global dispersion.